2022
DOI: 10.1007/s00371-022-02518-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling strokes in fast neural style transfer using content transforms

Abstract: Fast style transfer methods have recently gained popularity in art-related applications as they make a generalized real-time stylization of images practicable. However, they are mostly limited to one-shot stylizations concerning the interactive adjustment of style elements. In particular, the expressive control over stroke sizes or stroke orientations remains an open challenge. To this end, we propose a novel stroke-adjustable fast style transfer network that enables simultaneous control over the stroke size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To demonstrate our excellent performance, we compared out method with several state-of-the-art methods, including WCT2 [36], AdaIN [37], Johnson [16], StyTr2 [9], Style-TUNE [38] and Gatys [1]. As shown in Figure 3, it is observed that our method improves the quality of style-transferred images significantly.…”
Section: Visual Comparisonmentioning
confidence: 94%
“…To demonstrate our excellent performance, we compared out method with several state-of-the-art methods, including WCT2 [36], AdaIN [37], Johnson [16], StyTr2 [9], Style-TUNE [38] and Gatys [1]. As shown in Figure 3, it is observed that our method improves the quality of style-transferred images significantly.…”
Section: Visual Comparisonmentioning
confidence: 94%
“…It can simultaneously control stroke intensity and size. The experimental results showed that the model make users achieving resolutions exceeding 20 million pixels and good output fidelity [11]. Hollandi et al developed a deep learning-based cell nucleus segmentation framework that utilizes image style transfer to automatically generate cell nucleus segmentation masks.…”
Section: Jing Et Al Proposed a New Normalization Module Calledmentioning
confidence: 99%
“…From the initial single-model single-style algorithm to single-model multi-style algorithm, subsequently, 2 14 a large number of CNN-based arbitrary style image migration methods have been proposed, and this technological breakthrough has made style migration more flexible and practical. To enhance the style expression, some of them start from the brushstroke, 15 17 which generates meaningful stroke parameters in the vectorized environment, which are used to control the stroke size as well as the intensity, and further render the texture to present the unique brushstroke characteristics of the artist. However, obtaining many artists’ brushstrokes is not easy.…”
Section: Introductionmentioning
confidence: 99%